The relationship between strength asymmetries and jumping performance in professional volleyball players - Schons, P.; Gomes Da Rosa, R.; Fischer, G.; Pereira Berriel, G.; Gassen Fritsch, C.; Nakamura, F. Y.; Baroni, B. M.; Peyré-Tartaruga, L. A. (Sports Biomechanics, 2019)
Knee peak torque (PT) is associated to jump performance in volleyball players. It is not clear whether muscle strength imbalances of the knee joint can influence jump performance. The purpose of study was to analyse the association between PT and knee muscular imbalances with jump performance in professional volleyball players. Eleven elite male volleyball players (90.3 ± 9.7 kg body mass and 1.94 ± 0.06 m height) were evaluated in an isokinetic dynamometer at speeds of 60, 180 and 300 deg/s. Muscle strength imbalances were obtained through calculation of contralateral deficit between limbs and the conventional ratio (hamstrings/quadriceps). Countermovement jump (CMJ) was performed on a force plate to calculate mechanical power and height. Association was found between knee extensor PT at 180 deg/s with CMJ power (r = 0.610, p = 0.046). Conventional ratio at 300 deg/s showed negative association with CMJ (r = -0.656, p = 0.029). The optimal ratio between knee extensors PT in relation to the flexors PT is associated with the greater mechanical power in CMJ. Contralateral deficit does not seem to be associated with the CMJ performance. Considering the knee extensor PT is associated with CMJ power, our findings suggest that strength-based training in volleyball athletes should not omit the conventional muscle ratio.